Radio Ownership, Programme Sponsorship and Language of Delivery as Predictors of Citizens’ Participation in Community Development Projects in Oyo and Ogun States, Nigeria (2012)
Low communal and individual participation in community development (CD) programme has become worrisome to development planners and stakeholders. This situation has been attributed in part to inappropriate usage of the radio in mobilising the people for CD, though there are several studies on the use and importance of radio in development generally. This study, therefore, examined the extent to which radio ownership, programme sponsorship and language of delivery predicts citizens‟ participation in CD in Oyo and Ogun States, Nigeria. The study adopted the survey research design. Stratified and random sampling techniques were used to select a total of 1260 respondents comprising: 20 project officers, 73 government officials, 37 corporate public and governmental sponsors, 1120 listeners, 5 presenters and 5 producers, each from 5 radio stations in Oyo and Ogun States. Data were collected using Citizen Participation Scale (r = 0.76) and Radio Effectiveness Inventory (r = 0.81). These were complemented with four sessions of Key Informant Interviews (KII) and six sessions of Focus Group Discussion (FGD) for presenters, producers, project officers and community change agents. Three research questions were answered and three hypotheses tested at 0.05 level of significance. Data were analysed using Mean, t-test, Pearson Product Moment Correlation and Multiple regression. Radio ownership, programme sponsorship and language of delivery significantly influenced citizens‟ participation in CD (F(3,1257) = 202.8, p<0.05) and contributed 13.9% to the variance of the dependent variable. The relative contribution of these radio media components were as follows: language of delivery (β = 0.661, p<0.05), sponsorship (β = 0.614, p<0.05), period of airing the programme (β = .058, p<0.05), and ownership of station (β = 0.051, p<0.05). Significant differences exerted in the usage of radio for CD between public and private radio stations (t = 7.85, p<0.05). Result also showed differences in sponsorship of radio CD programmes: governmental (x= 40.41), corporate (x= 31.70); individual ( x = 25.23). Significant differences were observed in the usage and effectiveness of language of delivery of CD programmes on radio: Yoruba ( x = 45.96); English ( x = 29.17). Demographic variables included age (r = 0.72), marital status (r = 0.44), educational qualification (r = 0.42), occupation (r = 0.42) and sex (r = 0.31). These correlated significantly with citizens‟ participation of radio effectiveness for CD (R=0.78). The FGD and KII results showed that radio ownership, programme sponsorship and language of delivery were potent factors in enhancing citizens‟ participation in community development projects. The indigenous language of delivery (Yoruba), governmental sponsorship of community development programmes, public ownership of radio station, and period of airing the programme were significant factors in determining the success of radio media in mobilizing people for effective participation in CD. Therefore, government and other stakeholders should greatly consider these components of radio usage in all developmental processes to ensure maximum and effective participation of the citizenry in all developmental programme